2013
DOI: 10.1016/j.diamond.2013.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Diamond dosimeter for small beam stereotactic radiotherapy

Abstract: Recent developments of new therapy techniques using small photon beams, such as stereotactic radiotherapy, require new detectors to precisely determine the delivered dose. The dosimeter has to be as close as possible to tissue equivalence and exhibit a small detection volume compared to the size of the irradiation field, because of the lack of lateral electronic equilibrium in small beam. Characteristics of single crystaldiamond (tissue equivalent material Z = 6, high density) make it an ideal candidate to ful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 31 publications
0
15
0
1
Order By: Relevance
“…The use of research SCDDs has been reported [6][7][8] in conjunction with conventional linear accelerators, with square field sizes from 100 3 100 mm 2 down to 10 3 10 mm 2 as a measured at a 1000-mm source-to-detector distance (SDD). In this work, we present the results using a dedicated stereotactic linear accelerator with circular fields for fixed collimators ranging from 5 to 60 mm, at a nominal SDD of 800 mm, in a 6-MV unflattened photon beam.…”
Section: Methodsmentioning
confidence: 99%
“…The use of research SCDDs has been reported [6][7][8] in conjunction with conventional linear accelerators, with square field sizes from 100 3 100 mm 2 down to 10 3 10 mm 2 as a measured at a 1000-mm source-to-detector distance (SDD). In this work, we present the results using a dedicated stereotactic linear accelerator with circular fields for fixed collimators ranging from 5 to 60 mm, at a nominal SDD of 800 mm, in a 6-MV unflattened photon beam.…”
Section: Methodsmentioning
confidence: 99%
“…The characteristics of the synthetic diamond detector (PTW-60019), such as small active volume (0.004 mm 3 ), near water-equivalence (Z eff = 6), and low energy dependence, make it an interesting candidate for small field dose measurements as demonstrated by many authors. [15][16][17][18][19] To our knowledge, no one demonstrated the feasibility of using this synthetic diamond for OFs measurement for LGKP. Profiles in the three directions were also measured for the 4 mm collimator.…”
Section: Introductionmentioning
confidence: 99%
“…Schottky diodes are expected to have very good linearity. Dose-rate linearities have been measured in singlecrystal CVD diamond detectors by a number of groups [6], [9], [22]- [28], several of whom determined a significant nonlinear response as a function of dose-rate [6], [9], [23], [27], [28]. A variety of methodologies were used, including varying the PRF, varying the source current in the case of X-ray sources, and varying the source to detector distance, which is the method that has been used here.…”
Section: Comparison With Microdiamondmentioning
confidence: 99%